(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2019)
Persons with disabilities suffer during their lives discrimination that leads them to be limited in the full exercise of their rights. The change that has taken place since the adoption of the Convention on the Rights of Persons with Disabilities (CPCD) has generated the obligation of the States to adapt their standards through the establishment of concrete inclusion actions. Nowadays, a high percentage of the world population has a disability, which denotes the importance of this debate for the International society. This article aims to provide an overview of the aspects that recognize the people with disabilities as subjects of law, specifically in the opportunities for access to a regular job. The purpose is to give a perspective on the real barriers faced by this group of people when they fully participate in the development of their lives. Offering a multidisciplinary perspective, highlighting the joint work with non-governmental organizations, specifically professionals in the area, through concrete actions to eradicate discriminatory policies and generate spaces for inclusion and equality from an early age.